SPECIFIC FEATURES OF SPEECH THERAPY GAME TECHNOLOGIES FOR SPEECH DISORDERS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article provides a scientific and theoretical analysis of the specific features of speech therapy game technologies used in speech disorders. The study highlights the importance of game technologies in correcting speech disorders, their role in increasing children's motivation and activating speech activity. It also highlights the structure of games that include articulatory, phonemic hearing, breathing and voice exercises, and the principles of their organization.